Progressive resistance training improving gait performance and mobility in acute and chronic stroke patients (Journal of the Pakistan Medical Association, 2020)
Abstract Stroke, a neurological disorder, leads to long-term disability thereby greatly affecting gait and mobility. The purpose of the current study was to investigate the effects of progressive resistance training in both acute and chronic stroke patients. A quasi interventional study was designed and 46 stroke patients were recruited through convenience sampling technique. Sample size was calculated using epi-tool. Patients who had cognitive problems, balance impairments and contractures were excluded from the study. The study was conducted from January to June 2018, at Rafsan Rehab & Research Centre, Peshawar. Progressive resistance exercises starting at 50 % of one repetition maximum (RM) were performed three days/week and for a total duration of nine weeks. Blind assessor measured readings at baseline and after nine weeks. Gait dynamic index (GDI), Six-Meter Walk Test (SMWT) and Five Times Sit-to-Stand (FTSTS) tools were used to collect the required data. Continuous....